E-marketing strategy - Ellis-Chadwick, Fiona (Henry Stewart Talks, 2010)
A well-planned e-marketing strategy can make the difference between being a winner or loser online, How to identify the strategic potential and critical factors that affect what a company might achieve online, Instructive framework that can help with the development of a coherent e-strategy and aid business planning
Archived at 2022/04/12